Experimental study on soil erosion under different soil composition using rainfall simulator - Akihiro Hamanaka; Takashi Sasaoka; Hideki Shimada; Shinji Matsumoto (Plant, Soil and Environment, 2019)
Soil erosion is one of the major environmental problems in open-cut mines in tropical regions. It causes negative impacts including the removal of nutrient-rich topsoil, destroys aquatic habitat, dam and pond siltation, clogs river by deposition of sediment, and causes water pollution in the rehabilitation process. Soil texture is an important factor to affect soil erosion. In this study, artificial rainfall experiment in the laboratory scale was conducted to clarify the mechanism of soil erosion under the different soil composition and to discuss the methods for minimizing soil erosion. The obtained results showed that the soil seal generated due to the presence of fine particle under high rainfall intensity is the main contributor to accelerate the soil erosion. Additionally, the surface coverage by the cover crops is the most effective measure to reduce soil erosion because both the coarse and fine contents runoff can be minimized while arranging of the slope angle is effective for reducing the runoff of coarse contents and the soil compaction is effective to reduce that of fine contents. Soil erosion can be minimized by selecting prevention method considering the type of soil because the prevention effect on soil erosion is different depending on the type of soil.